The study of electoral system in Malaysia in reference to the legal position in New Zealand / Cyrill Clade … [et al.] - Clade, Cyrill; Jalil, Fatin Dayana; Ishak, Muhammad Arif; Noor Adzman, Muhammad Syadzuwan (Faculty of Law, 2013)
The basis of this project paper is mainly on the electoral system. It involves the analysis of the electoral system of Malaysia in reference to the electoral system in New Zealand. There was one time that both the countries adopted the First Past the Post (FPP) system as their electoral system. However, recently New Zealand had changed their electoral system from the FPP system to the Mixed-Member Proportionate (MPP) system due to various reasons. Therefore, we will illustrates the comparison of the FPP and MMP system that might contribute to the changes taken by the New Zealand. Hopefully the information in the research paper might be useful to improve our country's current situation and change whatever is necessary to be a better country.